Graduate employability post-COVID-19: the case of a Malaysian public university - Kamaruddin M.I.H.; Ahmad A.; Husain M.A.; Abd Hamid S.N. (Emerald Group Holdings Ltd., 2024)
Purpose: This study presents an effort to identify and understand the impact of the coronavirus disease 2019 (COVID-19) pandemic on the graduate employability (GE) of Universiti Sains Islam Malaysia (USIM) final year students. It examines the readiness of USIM's final year students to the internship during the lockdown period, the readiness to join GE programs and also employment prospects in the future. Design/methodology/approach: A questionnaire survey was employed, and 1,445 USIM final year students participated in this study. Findings: The findings reveal that USIM final year students are ready to perform their internship even during the lockdown period. Besides, the students are also ready to join GE programs conducted by USIM, even while COVID-19 pandemic still currently occurs. Meanwhile, for the employment prospects in the future, results show that they believed that the employment prospects in the future after COVID-19 is low. In addition, academic background and internship areas exacerbate COVID-19's impact on the perceptions of USIM final year students on the employment prospects in the future. Originality/value: This study is believed to be a pioneering study in identifying the impact of COVID-19 on the GE. It also contributes by identifying students' readiness to perform their internship during lockdown period via work from home (WFH) approach as well as their perceptions on the employment prospects in the future. 2020, Emerald Publishing Limited.